2016
DOI: 10.1089/pho.2015.4031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Level Laser Therapy Applied Before Treadmill Training on Recovery of Injured Skeletal Muscle in Wistar Rats

Abstract: Objective: The aim of this study was to analyze the effects of low-level laser therapy (LLLT) when associated with treadmill training on the recovery of skeletal muscle, during two periods of rest after muscle injury in rats. Background data: Because of photostimulation, LLLT has been presented as an alternative for accelerating the tissue healing process. Materials and methods: Forty rats were divided into two groups (A and B) containing four subgroups each: GC (Control Group)-cryolesion untreated; EG (Exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Next, we analyzed the cross-sectional area of the myofibers in the injured area after the treatment trial. A statistically significant increase in myofiber cross-sectional area was found in rats in the Cells and Cells+Exercise groups compared with the Vehicle group (247.5 ± 10.7 µm 2 ; P < .001) (Figure 4, A and B). Moreover, the Cells+Exercise group showed the largest increase in size of myofibers (686.0 ± 11.6 µm 2 ), which was significantly higher than that in the Cells group (612.3 ± 21.4 µm 2 ; P = .001) demonstrating a synergistic effect of cell therapy and exercise in the treatment of injured skeletal muscle.…”
Section: Resultsmentioning
confidence: 90%
“…Next, we analyzed the cross-sectional area of the myofibers in the injured area after the treatment trial. A statistically significant increase in myofiber cross-sectional area was found in rats in the Cells and Cells+Exercise groups compared with the Vehicle group (247.5 ± 10.7 µm 2 ; P < .001) (Figure 4, A and B). Moreover, the Cells+Exercise group showed the largest increase in size of myofibers (686.0 ± 11.6 µm 2 ), which was significantly higher than that in the Cells group (612.3 ± 21.4 µm 2 ; P = .001) demonstrating a synergistic effect of cell therapy and exercise in the treatment of injured skeletal muscle.…”
Section: Resultsmentioning
confidence: 90%
“…Techniques used separately may have slower therapeutic responses, and therefore the synergistic use of vacuum therapy with laser therapy may enhance the quality and speed of the biological response in the rehabilitation process. Several studies1, 2, 7, 18 ) showed that mechanical stimulus such as therapeutic ultrasound1, 2 ) and physical exercise7, 18 ) were associated with laser therapy and showed significant synergistic effects on physical rehabilitation, including pain relief, accelerated tissue repair and increased physical function. Vacuum therapy is also a mechanical stimulus to potentiate laser therapy, leading to synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Laser is an acronym for Light Amplification by Stimulated Emission of Radiation. Laser therapy advanced significantly in the mid-1960s and to date has been used in the health area, such as medicine, dentistry and physiotherapy producing satisfactory results in treatments that require, for example, anti-inflammatory and analgesic action, as well as acceleration of tissue healing processes5,6,7 ) . Penetration of skin by light depends on the incident wavelength and optical properties of the biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the potential value of combining infrared radiation with treadmill training to further enhance muscle function in an animal model (Adabbo et al 2016) as well as clinical trial (Paolillo et al 2011). However, the potential long-term effects of infrared radiation and treadmill training on bone mass, to our knowledge, have not been investigated.…”
Section: Introductionmentioning
confidence: 99%